CORRELATION OF JUNIOR HIGH SCHOOL STUDENT’S VOCABULARY MASTERY AND READING COMPREHENSION - Kadek Gangga Dwi Putra; I Gde Putu Agus Pramerta; Ida Ayu Made Sri Widiastuti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
Vocabulary is needed in English reading comprehension. The correlation between vocabulary mastery and reading comprehension was concern to be figured out. There were 37 eighth-grade students of SMP (SLUB) Saraswati 1 Denpasar in the academic year 2022/2023 who participated in the study. Further, in collecting the data, the researchers used two kinds of tests: a cloze task for vocabulary mastery and a short answer task for reading comprehension. SPSS 25.0 program was utilized to analyze the data with the following steps: normality testing, homogeneity testing, Pearson Product Moment, and t-test. The result of this research showed that there was a significant correlation between vocabulary mastery and reading comprehension with an r value 0.675. In addition, it showed that the level correlation was sufficient because it was in the interval of 0.60-0.799. Therefore, it shows a significant correlation between the two variables: vocabulary mastery and reading comprehension. Further studies with a wide range of subjects are recommended to figure out the role of vocabulary in English learning.